2008
DOI: 10.1002/ajp.20565
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of fatal respiratory outbreaks and detection of a human‐related metapneumovirus in wild chimpanzees (Pan troglodytes) at Mahale Mountains National Park, Western Tanzania

Abstract: Over the past several years, acute and fatal respiratory illnesses have occurred in the habituated group of wild chimpanzees at the Mahale Mountains National Park, Tanzania. Common respiratory viruses, such as measles and influenza, have been considered possible causative agents; however, neither of these viruses had been detected. During the fatal respiratory illnesses in 2003, 2005 and 2006, regular observations on affected individuals were recorded. Cause-specific morbidity rates were 98.3, 52.4 and 33.8%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
3
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(146 citation statements)
references
References 50 publications
2
135
3
4
Order By: Relevance
“…We propose that the stronger these evolutionary constraints, the more difficult it becomes to occupy new niches within the current host species. For example, both the phylogenetic data presented here, as well as recent evidence of epidemic human respiratory viruses circulating among chimpanzees (12,13), suggest that the Paramyxoviridae seem particularly prone to cross-species transfers. This is consistent with results from an earlier study of paramyxovirus F proteins, which found that viruses infecting different host species but with similar tissue tropism and transmission routes (i.e., through the respiratory epithelium) were closely related (14).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We propose that the stronger these evolutionary constraints, the more difficult it becomes to occupy new niches within the current host species. For example, both the phylogenetic data presented here, as well as recent evidence of epidemic human respiratory viruses circulating among chimpanzees (12,13), suggest that the Paramyxoviridae seem particularly prone to cross-species transfers. This is consistent with results from an earlier study of paramyxovirus F proteins, which found that viruses infecting different host species but with similar tissue tropism and transmission routes (i.e., through the respiratory epithelium) were closely related (14).…”
Section: Discussionmentioning
confidence: 69%
“…For example, foot-and-mouth disease virus from pigs requires one amino acid replacement to replicate in guinea pigs (19), whereas avian influenza viruses may require as many as 13 mutations to productively replicate in mammals (20). The relatively frequent transfer of viral lineages between humans and other primates further illustrates this concept (12,13,21,22). It therefore seems reasonable to speculate that cross-reactive immune responses, coupled with the slim possibility that diverging viruses may acquire diverse and nonoverlapping niches within the same host, may represent an evolutionary barrier less easily traversed by the virus than that of infection of a novel host species, especially if the two hosts are closely related.…”
Section: Discussionmentioning
confidence: 99%
“…une blessure conséquente à une bagarre avec un autre individu) ou qu'il montre des signes modérés de maladie ou de blessure. (Kaur et al 2008 ;Köndgen et al 2008 ;Palacios et al 2011 ;Yoshida et al soumis), le virus humain herpes simplex , une maladie similaire à la polio (Goodall 1986 ;Kortlandt 1996), une maladie similaire à la rougeole (Hastings et al 1991), la gale (Kalema-Zikusoka et al 2002) et des helminthes entériques et des protozoaires (Hasegawa et al 2014 ;Parsons et al 2015). La proximité immédiate entre grands singes et humains est connue pour entrainer la transmission de bactéries comme Escherichia coli, Salmonella et Shigella ; les gorilles et chimpanzés qui vivent près des humains sont connus pour être porteurs dans leur tractus gastro-intestinal d'E.…”
Section: Meilleures Pratiques Lors Des Interventions Cliniquesunclassified
“…De façon similaire, il a été documenté que le métapneumovirus humain a provoqué une maladie chez les chimpanzés du PN de Mahale (Kaur et al 2008) ² L'application du principe de précaution en matière de santé des grands singes est justifiée : en d'autres termes, en l'absence de preuve scientifique qu'un agent pathogène ou qu'une action ou politique humaine représente ou non un risque ou un danger pour les grands singes, il est plus sûr de supposer que cet agent ou cette action pose un risque pour la santé des grands singes jusqu'à preuve scientifique du contraire.…”
Section: Thème Spécial : Les Maladies Respiratoiresunclassified
“…Human respiratory pathogens have been isolated from gorillas and chimpanzees habituated for research and tourism (Chi et al 2007;Kaur et al 2008;Palacios et al 2011).…”
Section: Diseasementioning
confidence: 99%